Book Review: How the Next Generation of Fiqh? - Muhammad Latif Fauzi (Millah: Journal of Religious Studies, 2008)
Title           : Muslim Legal Thought in Modern IndonesiaAuthor        : R. Michael FeenerPublisher    : Cambridge University PressYear          : 2007Pages        : 290 pp.ISBN-10     : 052187775X